Nitrogen deficiency tolerance and responsiveness of durum wheat genotypes in Ethiopia - Aga, Tesfaye Geleta; Abera, Fetien Abay; Tufa, Tesfaye Balemi; Abebe, Kebebew Assefa; Abeyo, Bekele G.; Ayana, Negash Geleta (Hindawi Limited, 2022)
Development of low-nitrogen (N) tolerant and N-responsive durum wheat genotypes is required since nitrogen efficiency has emerged as a highly desirable trait from economic and environmental perspectives. Two hundred durum wheat genotypes were evaluated at three locations under optimum (ON) and low (LN) nitrogen conditions to screen genotypes for low-nitrogen tolerance and responsiveness to an optimum N supply. The results showed significant variations among the durum wheat genotypes for low-N tolerance and responsiveness. The average reduction in grain yield under the LN condition was 48.03% across genotypes. Only 17% of the genotypes tested performed well (grain yield reduction <40%) under LN conditions. Based on the absolute grain yield, biomass yield, and normalized difference vegetative index value, on average, 32, 14, 17, and 37% of the tested genotypes were classified as efficient and responsive, efficient and nonresponsive, inefficient and responsive, and inefficient and nonresponsive, respectively. Considering the absolute and relative grain yield, biomass yield, normalized difference vegetative index values, and stress tolerance indices as selection criteria, 17 genotypes were chosen for subsequent breeding. Among the screening indices, geometric mean productivity, stress tolerance index, yield index, and stress susceptibility index exhibited positive and significant correlations with grain yield under both N conditions; hence, either of these traits can be used to select low-N-tolerant genotypes. The common genotypes identified as LN-tolerant and responsive to N application in this study could be used as parental donors for developing N-efficient and responsive durum wheat varieties.